Stars and numbers - Kunitzsch, Paul.
1 online resource (356 pages)
Keywords: The studies brought together in this second collection of articles by Paul Kunitzsch continue the lines of research evident in his previous volume (The Arabs and the Stars). The Arabic materials discussed stem mostly from the early period of the development of Arabic-Islamic astronomy up to about 1000AD, while the Latin materials belong to the first stage of Western contact with Arabic science at the end of the 10th century, and to the peak of Arabic-Latin translation activity in 12th century Spain. The first set of articles focuses upon Ptolemy in the Arabic-Latin tradition, followed by further ones on Arabic astronomy and its reception in the West; the final group looks at details of the transmission of Euclid's Elements.